EVALUATE THE SAFETY AND INITIAL RESULTS OF APPLYING THE TECHNIQUE OF TREATING LUNG CANCER BY MICROWAVE ABLATION UNDER THE GUIDANCE OF COMPUTED TOMOGRAPHY - Cung Van Cong,; Tran Thi Ly,; Do Minh Luan, (Tạp chí Y học Quân sự, 2022)
A retrospective, cross-sectional study to evaluate the safety and initial results of applying the technique of treating lung cancer by microwave ablation under the guidance of computed tomography in 30 patients with non-small cells primary lung cancer, at the National Lung Hospital, from June 2018 to August 2020. Results: The average age of patients was 61.9 ± 6.5 years; male/female ratio was 14/1; 56.7% of patients had a history of multimodality therapy. The features on computed tomography film: the average tumor size was 37.94 mm; most of the lung tumors have peripheral locations (84.0%), solid tumors (93.5%), have mediastinal lymph nodes (50.0%). The proportion of patients treated with microwave ablation under the guidance of computed tomography: 1 time (60.0%), 2 times (33.3%), and 3 times (6.7%). The average burning time for lung tumors was 13.67 ± 5.3 minutes. Damage response after performing microwave ablation under the guidance of computed tomography: 15/23 patients (65.2%) had complete tumor necrosis and 8/23 patients (34.8%) had necrosis, not a complete tumor. 36.7% of patients had complications and 36.7% of patients had unwanted reactions. The average hospital stay after performing microwave ablation under the guidance of computed tomography was 11.2 ± 4.6 days. The rate of local recurrence was 18.2%, the rate of new metastasis was 22.7%.